The Impact of Provincial Road Damage on Community Activities in Pataruman District, Banjar City - Ryan Alviansyah; Radian Tama Saputra; Rafli Al Bukhori (Program Studi Pendidikan Geografi Universitas Pattimura, 2026)
This study aims to identify the condition of provincial roads, the factors causing damage, and the social and economic impacts on the community in Pataruman District, Banjar City. The research was conducted on Mayjen Lili Kusumah Road, a provincial route that has experienced severe damage. A qualitative approach was used with field observations and interviews involving residents, traders, and road users. The results showed that the types of damage found include cracks, large potholes, asphalt waves, and peeling at the road edges. The main factors causing the damage are the high frequency of heavy vehicles passing through and poor drainage systems around the road. The impacts felt by the community include longer travel times, increased risk of accidents, higher vehicle maintenance costs, and reduced income for local traders due to decreased buyer mobility. Government repair efforts have been temporary and have not addressed the root causes. Therefore, comprehensive improvements are needed, focusing on technical aspects, drainage systems, and active community participation to restore road functionality and support the social and economic activities of local residents.